2012
DOI: 10.1159/000339369
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Therapy versus Fluvoxamine as a Second-Step Treatment in Obsessive-Compulsive Disorder Nonresponsive to First-Step Behavior Therapy

Abstract: Background: To compare the effectiveness of second-step treatment with cognitive therapy (CT) versus fluvoxamine in patients with obsessive-compulsive disorder (OCD) who are nonresponsive to exposure in vivo with response prevention (ERP). Methods: A 12-week randomized controlled trial at an outpatient clinic in the Netherlands comparing CT with fluvoxamine in OCD. Of 118 subjects with OCD treated with 12 weeks of ERP, 48 appeared to be nonresponders (Y-BOCS improvement score of less than one third). These non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…[16,19] One recent study found that, following nonresponse to a course of exposure and response prevention (ERP) in a sample of adults with obsessivecompulsive disorder, fluvoxamine was superior to cognitive therapy. [28] These findings further support the possibility of switching to medication after nonresponse to an initial course of CBT. However, careful consideration of risks and benefits in the context of available treatments as well as patient choice is needed in selecting second-stage treatments.…”
Section: Discussionmentioning
confidence: 60%
“…[16,19] One recent study found that, following nonresponse to a course of exposure and response prevention (ERP) in a sample of adults with obsessivecompulsive disorder, fluvoxamine was superior to cognitive therapy. [28] These findings further support the possibility of switching to medication after nonresponse to an initial course of CBT. However, careful consideration of risks and benefits in the context of available treatments as well as patient choice is needed in selecting second-stage treatments.…”
Section: Discussionmentioning
confidence: 60%
“…In the present study, a Y-BOCS score of 8 points or less constituted an exclusion criterion. The overall Y-BOCS SR score of 20.12 was lower than in other studies [65,66,67,68]. Therefore, participants with a low level of suffering were included, which did not leave much room for improvement.…”
Section: Discussionmentioning
confidence: 97%
“…Empirical studies on treatment-resistant patients are rare [3,4], and empirically based guidelines to advise clinicians on how to help treatment nonresponders are lacking. Very few randomized controlled trials have examined the effects of switching from a psychotherapy that failed to adequately work to a different psychotherapy.…”
Section: Introductionmentioning
confidence: 99%